Analisis kinerja bank pemerintah sebelum dan selama pandemi covid-19 - wahyuni, Iis (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
State-owned banks are able to provide nearly 50 percent of the net profit of the entire national banking sector. However, the Covid-19 pandemic that hit the face of the earth in early 2020 turned the development of the Indonesian government Bank upside down. As a result of this outbreak, state-owned banks experienced several problems, namely arrears in payments from customers, increased credit exposure, and decreased levels of liquidity, solvency and profitability. This study aims to examine differences in Third Party Funds (DPK), credit risk (NPL), liquidity (LDR), and profitability (ROA) of state-owned banks before and during the COVID-19 pandemic. This study used a comparative quantitative method with analytical techniques using the paired sample t-test and the Wilcoxon signed ranks test with the classical assumption test. The sampling technique used purposive sampling, then obtained 4 research samples, including Bank BRI, Bank Mandiri, Bank BNI, and Bank BTN. This study uses secondary data in the form of quarterly financial reports of government banks listed on the Indonesia Stock Exchange for the 2018-2021 period. The results of this study indicate that Third Party Funds (DPK), Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA) all experienced significant differences during the 2018–2019 period before the COVID-19 pandemic significant differences occurred during the COVID-19 pandemic (2020–2021).